The Relationship between Self-Esteem and Anxiety Levels in Final-year Medical Students - Adiwijaya, Janice Nathania; Felita, Fiona; Fitrikasari, Alifiati; Sarjana, Widodo; Hadiati, Titis (Diponegoro International Medical Journal, 2024)
Background: Self-esteem is an evaluation of oneself that can be positive or negative. Self-esteem affects the way individuals value and views themselves and others. Self-esteem increases gradually during young adulthood. On the other hand, anxiety disorders are also prone to occur during this time. Individuals with low self-esteem arefound to often experience symptoms of anxiety.Objective: The purpose of this study is to examine the relationship between self-esteem and anxiety levels among final year medical students, Faculty of Medicine, Diponegoro University.Methods: This research is a correlational analytic observational study with a cross-sectional design. Total sampling was used in this research involving final year medical students, Faculty of Medicine, Diponegoro University (Class of 2018). Self-esteem was assessed using the Rosenberg Self-esteem Scale (RSES), and anxiety levels were assessed using the Zung Self-rating Anxiety Scale (ZSAS) that had been tested valid and reliable. Data were analyzed using Spearman and Lambda Correlation Tests.Results: There were 226 respondents involved in this study. The majority of respondents had high self-esteem (69.5%) and a mild level of anxiety (84.1%). Gender was known to affect the level of anxiety (p=0.026) but not self-esteem. Academic achievement and residency status was known not to affect self-esteem and anxiety levels. There was a significant relationship (p=0.000) between self-esteem and anxiety levels with a moderate negative correlation (r=-0.289).Conclusion: There was a significant relationship between self-esteem and anxiety levels.